Antidiabetic, hypolipidemic, antioxidant and anti-inflammatory effects of Momordica charantia L. foliage extract. - Alicia Lagarto Parra; Roberto Menéndez Soto-del Valle; Janet Piloto Ferrer; Pham Thi Nguyet Hang; Nguyen Thi Phuong; Addis Bellma; Orestes Darío López; Dunia Casanave Guarnaluce; Carlos Rodríguez Ferrada; Alejandro S. Padrón Yaquis; Nicte González Alfonso; Gilberto L. Pardo-Andreu (GarVal Editorial Ltda., 2021)
Context: Momordica charantia (Cucurbitaceae) is extensively distributed in tropical areas, and it is traditionally used as antidiabetic. Nevertheless, few studies supporting the metabolic effects of its foliage extracts have been reported elsewhere. Aims: To evaluate the effects of M. charantia foliage extract (MCh) on blood glucose and lipids levels in animal models of hyperglycemia. The anti-inflammatory and antioxidant properties together with the acute toxicity and genotoxic effects were also assessed. Methods: An MCh powder was obtained by spray-drying techniques. The anti-hyperglycemic and hypolipidemic effects of MCh were evaluated in the glucose tolerance test and the alloxan-induced diabetes, respectively. The in vitro and ex vivo MCh antioxidant effects were assessed against the 2,2´-azinobis3-ethylbenzothiazoline-6-sulfonic acid (ABTS), peroxyl, and superoxide anion radicals. The MCh anti-inflammatory effects were also assessed together with its toxicological profile by means of the Acute Toxic Class Method, and the chromosome aberration assay. Results: MCh administered orally diminished the glucose and lipids levels in normoglycemic healthy rats and alloxan-induced hyperglycemic mice. Strong in vitro free radical scavenging effects was demonstrated by MCh against ABTS, peroxyl, and superoxide anion radicals. The extract also improved the free radical scavenging ability of diabetic mice serum. Moreover, MCh reduced the weight of cotton-induced granulomas in mice, the exudate volume, and its leukocyte counts in carrageenan-induced pleurisy in rats. Very low MCh toxicity was also verified. Conclusions: The hypoglycemic, hypolipidemic, anti-inflammatory, and antioxidant activities here observed make the spray-drayed powder from M. charantia foliage extract an interesting alternative for the correction of diabetes and its complications.